Dealing with conflict - Eunson, Baden (Milton, Qld : John Wiley and Sons, 1996)
Conflict. Conflict and stress. Conflict at the intrapersonal level: the conflicts within us. The assertiveness approach. The transactional analysis approach...
Keywords: Communication; Negotiation; Negotiation; Communication; Conflict management